A parallel-group, randomized controlled trial into the effectiveness of Mindfulness-Based Compassionate Living (MBCL) compared to treatment-as-usual in recurrent depression: Trial design and protocol - Schuling, R; Huijbers, M; van Ravesteijn, H; Donders, R; Kuyken, W; Speckens, A (Elsevier, 2016)
Mindfulness Based Cognitive Therapy (MBCT) has been shown to reduce the risk of relapse in patients with recurrent depression, but relapse rates remain high. To further improve outcome for this group of patients, follow-up interventions may be needed. Compassion training focuses explicitly on developing self-compassion, one of the putative working mechanisms of MBCT. No previous research has been done on the effectiveness of compassion training following MBCT in patients with recurrent depression.To investigate the effectiveness of Mindfulness-Based Compassionate Living (MBCL) in reducing (residual) depressive symptoms in patients with recurrent depression who previously participated in MBCT.A randomized controlled trial comparing MBCL in addition to treatment as usual (TAU) with TAU only, in patients suffering from recurrent depressive episodes who completed an MBCT course in the past. Assessments will take place at baseline, post-treatment and at six months follow-up. After the control period, patients randomized to the TAU condition will be offered MBCL as well.Primary outcome measure is severity of depressive symptoms according to the Beck Depression Inventory-II (BDI-II) at post-treatment. Secondary outcome measures are presence or absence of DSM-IV depressive disorder, rumination, self-compassion, mindfulness skills, positive affect, quality of life, experiential avoidance and fear of self-compassion.Our study is the first randomized controlled trial to examine the effectiveness of compassion training following MBCT in a recurrently depressed population.ClinicalTrials.gov: NCT02059200, registered 30 January 2014.